The Effect of Internal Control Systems, Village Government Competence, Financial Report Transparency, and Financial Report Accessibility on The Accountability of Village Funds in the Pangkah Subdistrict - Almishri, Affan (Jurnal Indonesia Sosial Sains, 2026)
This research aims to analyze influence system internal control, competence government village, transparency report finance, and accessibility report finance to accountability village fund management in the sub-district Pangkah, Tegal Regency. Research This use approach quantitative with method descriptive. Population in study This is all over villages in the sub-district Pangkah, totaling 23 villages, with saturated sampling technique so that all over population made into sample. Amount respondents consisting of 92 people from head village, secretary village treasurer​ village, and the head of the Village Consultative Body. The data used is the primary data obtained through distribution questionnaire with Likert scale. Data analysis techniques were carried out using data quality tests, assumption tests classical, as well as hypothesis testing in the form of t-test, F-test, and coefficient determination with help application statistics. The research results show that system internal control, competence government village, transparency, and accessibility report finance influential to accountability village fund management. Findings This indicates that the more Good implementation fourth variables said, then the more tall level accountability in village fund management